Halvorsenius exilis gen. et sp. nov., a new didymozoid trematode from the mackerel Scomber scombrus L - Gibson, D. I.; MacKenzie, K.; Cottle, J. (Journal of Natural History, 1981)
A new genus and species of nematobothriine didymozoid, Halvorsenius exilis, is described. These worms occur unpaired and unencysted in the connective tissue of the mackerel Scomber scombrus, especially in the pericardium, the ‘throat’ region, the orbits and the region of the kidneys. Halvorsenius belongs to a group of genera which possess three uterine loops and two testes, but can be distinguished by the atrophy of the gut and other features. Live worms occur only in young mackerel, although aggregations of eggs are found in older fish. It appears that the eggs are retained in utero until the death of the worm and that there is no obvious mechanism for voiding the eggs from the fish other than through the death of this host.